Pemanfaatan Story Board Untuk Media Pendukung Dalam Meningkatkan kualitas Pembelajaran Anak di TK Islam Cikal Cendekia - Ari Hidayatullah; Irfan Nurdiansyah; Muhammad Patria (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2026)
This community service activity was carried out as an effort to improve the quality of learning at TK Islam Cikal Cendekia, particularly in developing creative technology-based visual media. The urgency of this activity arises from the condition that most visual media supporting storytelling used in early childhood education have limited variation and do not adequately contextually represent character values within the school environment. Through the utilization of Artificial Intelligence (AI) technology, teachers can creatively develop new educational storyboards aligned with learning themes without requiring complex visual design skills.The objectives of this activity are to: (1) enhance teachers’ digital literacy and creativity in developing learning media, (2) introduce and train teachers in the use of the Gemini (Gem) platform as an innovative tool for generating ideas, scripts, and automatic storyboard visualizations, (3) produce a collection of thematic storyboards created by teachers for use in early childhood learning activities, and (4) strengthen the school’s identity through original and contextual learning media. The implementation method consists of five main stages: program socialization, storyboard creation training using Gemini (Gem), classroom implementation of the storyboards, mentoring and evaluation, and program sustainability through the formation of a teacher creative team. The approach is participatory, involving teachers as the main actors, supported by a team of lecturers and students from Universitas Dian Nusantara.The targeted outputs include: (1) the creation of at least five character-themed educational storyboards developed by teachers, (2) improved digital and pedagogical competencies of teachers, (3) a practical guide for using Gemini (Gem) in early childhood education, and (4) an activity report and publication of results in the school’s internal media.